Cladistic analysis of the suborder Conulariina Miller and Gurley, 1896 (Cnidaria, Scyphozoa; Vendian-Triassic) - Leme, Juliana de Moraes [UNESP]; Simões, Marcello Guimarães [UNESP]; Marques, Antonio Carlos; Van Iten, Heyo (Wiley-Blackwell, 2008)
Results of a cladistic analysis of the suborder Conulariina Miller and Gurley, 1896, a major extinct (Vendian-Triassic) group of scyphozoan cnidarians, are presented. The analysis sought to test whether the three conulariid subfamilies (Conulariinae Walcott, 1886, Paraconulariinae Sinclair, 1952 and Ctenoconulariinae Sinclair, 1952) recognized in the Treatise on Invertebrate Paleontology ( TIP) are monophyletic. A total of 17 morphological characters were scored for 16 ingroup taxa, namely the genera Archaeoconularia, Baccaconularia, Climacoconus, Conularia, Conulariella, Conularina, Ctenoconularia, Eoconularia, Glyptoconularia, Metaconularia, Notoconularia, Paraconularia, Pseudoconularia, Reticulaconularia, Teresconularia and Vendoconularia. The extant medusozoan taxa Cubozoa, Stauromedusae, Coronatae and Semaeostomeae served as outgroups. Unweighted analysisof the data matrix yielded 1057 trees, and successive weighting analysis resulted in one of the 1057 original trees. The ingroup is monophyletic with two autapomorphies: (1) the quadrate geometry of the oral region; and (2) the presence of a mineralized (phosphatic) periderm. Within the ingroup, the clade (Vendoconularia, Teresconularia, Conularina, Eoconularia) is supported by the sinusoidal longitudinal geometry of the transverse ridges, and the much larger clade (Baccaconularia, Glyptoconularia, Metaconularia, Pseudoconularia, Conularia, Ctenoconularia, Archaeoconularia, Notoconularia, Climacoconus, Paraconularia, Reticulaconularia) is supported by the presence of external tubercles, which, however, were lost in the clade (Notoconularia, Climacoconus, Paraconularia, Reticulaconularia). As proposed by Van Iten et al. (2000), the clade (Notoconularia, Climacoconus, Paraconularia, Reticulaconularia) is supported by the termination and alternation of the transverse ribs in the corner sulcus. The previously recognized subfamilies Conulariinae, Paraconulariinae and Ctenoconulariinae were not recovered from this analysis. The diagnostic features of Conulariinae (continuation of the transverse ornament across the corner sulcus and lack of carinae) and Ctenoconulariinae ( presence of carinae) are symplesiomorphic or homoplastic, and Paraconulariinae is polyphyletic. The families Conulariellidae Kiderlen, 1937 and Conulariopsidae Sugiyama, 1942, also recognized in the TIP, are monogeneric, and since they provide no additional phylogenetic information, should be abandoned.
Keywords: conulariids; phylogeny; systematics; Conulariina; Cnidaria; Medusozoa; Phanerozoic